Predicting Early Literacy: Auditory and Visual Speech Decoding in Deaf and Hard-of-Hearing Children. (12th July 2022) - Couvee, Sascha; Wauters, Loes; Verhoeven, Ludo; Knoors, Harry; Segers, Eliane
Abstract: The current study investigated the relative contributions of auditory speech decoding (i.e., auditory discrimination) and visual speech decoding (i.e., speechreading) on phonological awareness and letter knowledge in deaf and hard-of-hearing (DHH) kindergartners ( M age = 6;4, n = 27) and hearing kindergartners ( M age = 5;10, n = 42). Hearing children scored higher on auditory discrimination and phonological awareness, with the DHH children scoring at chance level for auditory discrimination, while no differences were found on speechreading and letter knowledge. For DHH children, speechreading correlated with phonological awareness and letter knowledge, for the hearing children, auditory discrimination correlated with phonological awareness. Two regression analyses showed that speechreading predicted phonological awareness and letter knowledge in DHH children only. Speechreading may thus be a compensatory factor in early literacy for DHH children, at least for those who are exposed to spoken language in monolingual or in bilingual or bimodal-bilingual contexts, and could be important to focus on during early literacy instruction.